Surveillance | Society | Culture - Zappe, Florian; Gross, Andrew S. (Contributions to English and American Literary Studies (CEALS), 2020)
What only a few decades ago would have been considered a totalitarian nightmare seems to have become reality: Surveillance practices and technologies have infiltrated all aspects of our lives, forcing us to reconsider established notions of privacy, subjectivity, and the status of the individual in society. The United States is central to contemporary concerns about surveillance. American companies are at the forefront of developing surveillance technologies; and government agencies, in the name of security and law and order, are monitoring our words and actions more than ever before. This book brings together an interdisciplinary group of scholars to explore the implications of what many consider to be a far-reaching social, political, and cultural transformation.